Hubungan Komunikasi Terapeutik Perawat dengan Kepuasan Pasien di Ruang Rawat Inap Rumah Sakit Grha Permata Ibu Tahun 2025 - Ida Farida; Ahmad Rizal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The quality of nursing services is not solely determined by nurses’ technical competence in providing clinical care, but is also influenced by their ability to establish therapeutic communication with patients. Therapeutic communication is a professional interaction process aimed at helping patients understand their health conditions, express their feelings, and develop a trusting relationship with nurses. Effective communication between nurses and patients can increase patients’ comfort during hospitalization and may influence their level of satisfaction with the nursing services provided. This study aimed to determine the relationship between nurses’ therapeutic communication and patient satisfaction in the inpatient ward of Grha Permata Ibu Hospital in 2025. This study used an observational analytic design with a cross-sectional approach. The sample consisted of 182 patients selected using a purposive sampling technique. Data were collected using a therapeutic communication questionnaire and the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) to assess patient satisfaction with nursing care. Data analysis was conducted using the Spearman Rank correlation test to determine the relationship between the two variables. Most respondents assessed nurses’ therapeutic communication as good (87%). However, the majority of patients reported poor satisfaction levels (79.7%). The results of the Spearman Rank analysis showed a Sig. (2-tailed) value of <0.001 with a correlation coefficient of rs = −0.438, indicating a statistically significant relationship with a moderate correlation strength between nurses’ therapeutic communication and patient satisfaction. There is a significant relationship between nurses’ therapeutic communication and patient satisfaction in the inpatient ward of Grha Permata Ibu Hospital.